Meio ambiente e desenvolvimento: a construção do debate ambiental em O Correio da UNESCO (1972-1992) - Peguim, Cássia Natanie [UNESP] (2015)
We have observed that over the last four decades of the twentieth century, the formulation of environmental issues has emerged as a cause and symptom of a state of mind marked by the questioning of economic growth and the use of natural resources. Revealing a temporal and conceptual review process of human actions on nature, which incorporates the inconclusive debate about environment and development. In this paper we seek to elaborate on the debate that the magazine The UNESCO Courier proposes on these topics between 1972 - the year of the beginning of the publication of the magazine in Portuguese and the United Nations Conference on the Human Environment; and 1992 - the year of the United Nations Conference on Environment and Development. The discussions included in this magazine are studied from the perspective of Environmental History, particularly about the perception of the process of appropriation/transformation/destruction of the natural world over time. The magazine The UNESCO Courier contains articles that disclose and discuss the programs that United Nations of the Education, Science and Culture Organization - UNESCO had developed to address environmental issues in the areas of water resources, ocean research, conservation of the environment and natural heritage safeguarding. These programs were based on the ideal of the information exchange and scientific cooperation. Thus the magazine, conceived as a window for the world, is presented as a space of free information flow whereby UNESCO itself and its Member States express their perceptions about the environment. Perceptions pervaded by utilitarianism and validity of natural resources to promote development. Concept that The UNESCO Courier presents with continuous readings and displacements, but linked to UNESCO's ability to catalyze the demands of the Member States and to foster initiatives directed towards science and technology in...